The influence of short-term diabetes mellitus and insulin therapy on alveolar bone loss in rats - Holzhausen, M.; Garcia, D. F.; Pepato, M. T.; Marcantonio, E. (Blackwell Munksgaard, 2004)
Background: It is well known that the multiple direct and indirect consequences of hyperglycemia in diabetic individuals have been linked to a number of abnormal host effector mechanisms that could lead to an increased risk of developing periodontal disease.Objective: the aim of this study was to investigate the effect of short-term experimental diabetes and insulin therapy on the severity of alveolar bone loss in rats, and the effect of experimental periodontitis on glycemic control.Methods: Seventy-two male Wistar rats were divided into four groups: group I animals were submitted to dental ligature around lower right first molars (ligated); group II consisted of streptozotocin (STZ)-diabetic, ligated rats; group III represented STZ-diabetic, unligated rats; and group IV consisted of insulin-treated (6 U/day), STZ-diabetic, ligated rats. Blood glucose of all diabetic rats was monitored at regular intervals. Standardized digital radiographs were taken after killing at 7, 15 and 30 days to measure the amount of bone loss about the mesial root surface of the first molar tooth in each rat.Results: No significant (p < 0.05) changes in plasma glucose levels of insulin-treated diabetic rats were found among the different examinations after the beginning of insulin therapy. Rats from group II showed significantly greater increases in mean plasma glucose levels at 15 and 30 days after ligature placement compared with rats from group III (p < 0.05). Furthermore, in spite of the significant alveolar bone loss progression that was observed in groups I, II and IV (p < 0.00001; two-way ANOVA), no significant differences among these groups regarding the severity of bone loss (p = 0.77) and no significant interaction between treatment group and time (p = 0.81) were found.Conclusions: Within the limits of this study, it can be suggested that the severity of periodontal disease was not affected by short-term diabetes, and that experimental periodontitis increased blood glucose levels in uncontrolled diabetic rats.
Keywords: alveolar bone loss; diabetes mellitus; etiology; hyperglycemia; insulin therapy; periodontal diseases; progression